Rozvíjení matematické gramotnosti s využitím inovativního modulu systematického rozvoje akcelerovaných žáků 1. až 3. tříd Metodický text pro učitele - Nováková, Eva (Masaryk University Press, 2022)
Title in English: Developing mathematical literacy using an innovative module for the systematic development of accelerated pupils in grades 1 to 3: Methodical text for teachers The methodological text is an output of the three-year project "Research-validated innovative model of identification and development of mathematically gifted primary school pupils (VOIM)". The modernly designed development materials are designate primarily for pupils of the first grade who like to think, explore, discover new knowledge (not only) in the field of mathematics. 60 worksheets in three levels of difficulty for 20 mathematical topics are accompanied by a set of videos. The worksheets enable differentiated individual work of pupils. The tasks lead to the development of their abstract and exact thinking, critical reasoning and argumentation. The tasks are based on current curriculum documents but go beyond the educational content in some places. The difficulty of the tasks on each worksheet grades from the least difficult to the most difficult, usually from the extension curriculum.